PTU-335 Quality of care in the management of inflammatory bowel disease: how do patients rate their quality of care?. (22nd June 2015) - Ding, WY; Baigent, A; Bunger, K; Dibb, M; Ellis, T; Gordon, M; Probert, C; Subramanian, S; Collins, P
Abstract : Introduction: QUOTE-IBD is a validated patient questionnaire that assesses the quality of health care provision in inflammatory bowel disease (IBD) from the patient's perspective. 1 A series of questions assess health care within eight domains. Each patient scores elements of their health care according to: 1) The importance of that aspect of health care to them, and 2) Their experience as to how well that aspect of the service is delivered. The QUOTE instrument combines the "Importance" and "Performance" scores to generate a "Quality Impact" (QI) score for each domain (range 0 to 10). A QI of less than 9.0 indicates that there is room for improvement. Patients scored health care provision for specialist clinics and GP attendances separately. Aim: To assess the quality of health care provision from the IBD service in a tertiary centre from patients' perspective. Method: The QUOTE-IBD questionnaire was given to consecutive patients in three consecutive IBD clinics. Data were analysed as described by van der Eijk et al . 1 Results: 149 consecutive patients were invited to complete the QUOTE-IBD questionnaire with a response rate of 98.7%. 59 patients (40.1%) indicated that they had a diagnosis of Crohn's disease, and 49 patients (33.3%) a diagnosis of ulcerative colitis (33.3%). 39 patients (26.6%) did not indicate an IBD-subtype. Specialist clinics and GP services had QI scores of > 9.0 for accommodation and cost, with specialist clinics also scoring >9.0 for courtesy. Overall there was a trend for specialist-led clinics to have higher QI scores than GP-based services for IBD care. With the exception of one domain, all QI scores were >8.0. The aspect of health care rated lowest for quality provision was in the domain of provision of information. Subjective feedback supported this latter observation, with requests for information on diet as a common theme. Conclusion: Patients attending a tertiary IBD service express a high level of satisfaction with their health care. Feedback indicates areas where there is room for improvement, with provision of information deemed the area requiring greatest focus. (Patient information packs have been developed in partnership with the patient panel.) The QUOTE-IBD tool is a valuable resource to enhance patient-centred improvement in the quality of health care in IBD. Disclosure of interest: None Declared. Reference: van der Eijk et al . Am J Gastroenterol. 2001;96:3329